(untitled) (Reflection and Critique Law Magazine, 2022)
The present article deals with the The Penalty of Deprivation of Liberty and the prison, evidencing its effects in the execution of the sentence. Through bibliographic review, aspects such as stigma, prejudice and prison effects will be addressed, also analyzing some effects observed from Drauzio Varella’s work Os Carcereiros. Expanding the study of the sentence and its implications, conveniently restricted to a condemned person and which are sometimes superficial answers, it is asked: who is hit by the Penalty of Deprivation of Liberty? What are the effects of the intramural and extramural prison? What are the effects of prisonization on the prisioner’s family? In a synthetic opening and in a unexhausted manner, the purpose of this article will be to clarify, at the first moment, to what extent The Restrictive Penalty of Freedom goes and who is achieved, even if indirectly, by it. And in a second step, it is demonstrated the effects of prisonization on the execution of the sentence, not only on the condemned, but also on the family members. The conclusion is that the prison cause irreparable sequels, of all kinds, affecting them biologically, socially and psychologically, during and after the imprisonment, with the doctrine remaining only an inaccuracy as to the extent of these effects.